The potential of stingless bees cultivation with agroforestry techniques in “Kebun Sidang” Antutan Village, Bulungan District, Indonesia - Marjenah, Marjenah; Harmonis, Harmonis; Orvalinda, Ona (ULIN: Jurnal Hutan Tropis, 2025)
Honey, which is generated by honey bees, is one of the prominent non-timber forest products among the population. The stingless bee is the species of bee that has the most potential for cultivation (local name: Kelulut). The stingless bee is the species of bee that has the potential to be domesticated. The stingless bee is a little black insect with a 3 to 4 mm body length and an 8 mm wing span. This study sought to identify the pattern of agroforestry in the evolution of stingless bee cultivation. To determine the plant types and possibilities for stingless bee feed, as well as the viability of growing stingless bee agriculture in the Community Forest of Antutan Village, Bulungan Regency. The descriptive approach and interviews and field surveys are utilized for sample purposes. The results revealed that the applied agroforestry pattern was meliponiculture, or the production of stingless bees in conjunction with plantations and agriculture. There are nine plant species with a total of 64 individuals that could serve as stingless bee food. For the business feasibility value, the R/C ratio is 1.9 and the B/C ratio is 0.9, which shows that the firm is both profitable and possible to operate.